The absurd of the human condition in Sartre and Camus - Naranjo Cobo, Pedro; Peña, Alejandro G. J. (Pensamiento. Revista de Investigación e Información Filosófica, 2024)
In this paper, we postulate that in the philosophical systems of Sartre and Camus, we can observe an acknowledgement of human existence as absurd, conceived as an ontological condition of being-for-itself in the former, and as a discrepancy between our craving for meaning in the world and the world´s indifference in the latter. By carrying out an hermeneutic comparison, we will conclude that the absurd in Sartre forces us to create our essence while we exist and we can transcend it, whereas in Camus, the absurd is insurmountable, but grasping it is our only option for living with such condition.